Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Albert Watkins and Pauline Gibson Shoemaker by headstone of Henry and Mary Analiza Watkins Prospect Cemetery, west of Cleveland, TN